Velocity of nerve conduction of the tibial and peroneal nerves of Jordan's national badminton team - Nedal Banysaeed; Mohammad Bani Melhim; Aseel Najadat (Universidad de Murcia, 2024)
This study aimed to identify velocity of nerve conduction of the tibial and peroneal nerves of the lower end. This was an experimental study and the sample consisted of two groups: the experimental group (A) which consisted of 10 badminton players and their average age was 20-+70 years, regulated in training and every one of them plays with his right hand from the Jordan national badminton team players, and the second, the control group (B), who didn't practice any physical activity, and their number was (10) who are healthy with average age (20+-60). The results revealed statistically significant differences at ( ≥α 0.05) between the variables velocity of nerve conduction of the tibial nerves and peroneal nerves for the experimental group, there were no statistically significant differences at (≥α 0.05) in the velocity of nerve conduction of the tibial nerves and peroneal nerves according to the variable of age, whereas there were statistically significant differences at ( ≥α 0.05) between the variables velocity of nerve conduction of right peroneal nerves according to the variable of years of experience, where these differences were for people who have experience of more than 5 years.